PENURUNAN INDEKS GINI PENDIDIKAN: INDONESIA, JAWA TENGAH DAN MAGELANG - Budiono Budiono (Universitas Pembangunan Nasional Veteran Yogyakarta, 2020)
This policy paper aims to determine the relationship between educational inequality and the average length of schooling in Indonesia, Central Java Province and Magelang District. The data source is the national socio-economic survey (Susenas / BPS) in 2015 and 2020, especially the table: the percentage of the population aged 15 years and over according to the type of area and the highest level of education completed. To determine education inequality, it is calculated using data on the average length of schooling of the population aged 15 years and over, the Lorenz curve and the Gini index of education. The average length of schooling in Indonesia, Central Java Province, Magelang Regency increased during the 2015–2020 period, while education inequality decreased. The Gini index calculation results show that Indonesia is more evenly distributed than Central Java, and Magelang is the least even. A negative relationship was found between mean years of schooling and the Gini index of education. a positive relationship was found between the rate of increase in mean years of schooling and a decrease in the Gini index of educationNaskah kebijakan ini bertujuan untuk mengetahui hubungan antara ketimpangan pendidikan dengan rata-rata lama sekolah di Indonesia, Provinsi Jawa Tengah dan Kabupaten Magelang. Sumber data adalah surve social ekonomi nasional (Susenas / BPS) tahun 2015 dan 2020, khusunya tabel: persentase penduduk usia 15 tahun ke atas menurut tipe daerah dan jenjang pendidikan tertinggi yang ditamatkan. Untuk menentukan ketimpangan pendidikan dihitung melalui, data rata-rata lama sekolah penduduk usia 15 tahun ke atas, kurva Lorenz dan indeks Gini pendidikan. Rata-rata lama sekolah di Indonesia, Provinsi Jawa Tengah Kabupaten Magelang meningkat selama periode 2015–2020 sedangkan ketimpangan pendidikan menurun. Hasil perhitungan indeks gini menunjukan bahwa Indonesia lebih merata daripada Jawa Tengan, dan Magelang paling tidak merata. Hubungan negatif ditemukan antara rata-rata tahun sekolah dan indeks Gini pendidikan. hubungan positif ditemukan antara tingkat kenaikan rata-rata tahun sekolah dan penurunan indeks Gini pendidikan.